Efficiency Analysis of Financial And Non-Financial Performance At Nu Care-LAZISNU East Java - Rany Dinda Damara; Hastanti Agustin Rahayu (Tazkia Islamic Finance and Business Review, 2023)
The purpose of this research is to describe how the level of financial and non-financial performance is implemented by the NU Care-LAZISNU Regional Management of East Java Province based on efficiency ratios.In this study using a descriptive qualitative method approach. Primary and secondary data were obtained directly from NU Care-LAZISNU East Java through interviews, documentation and observation techniques which were then processed and analyzed to draw conclusions. The results of this study indicate that the level of efficiencythe financial performance of NU Care-LAZISNU East Java for the period 2017-2021 in the efficiency ratio for non-program activities experienced fluctuations and the efficiency ratio for program activities experienced efficiency consistency. While the efficiency level of non-financial performance of NU Care-LAZISNU East Java is based on the efficiency ratio of internal business processes in accordance with the existing priority scale, namely always paying attention to external and internal environmental conditions to minimize risk, while the efficiency ratio of resource providers in retention and acquisition of resource providers power (Muzakki) is stated to be inefficient, due to the bad turnover of muzakki from 2017-2021. Keywords: Efficiency, Financial Performance, Non-financial Performance, NU Care-LAZISNU East Java.